Consuming modernity : gendered behaviour and consumerism before the baby boom - Warsh, Cheryl Krasnick, 1957-; Malleck, Dan (UBC Press, 2013)
"In times of war, political strife, and economic recession, governments often call upon their citizens to get out and shop, reasoning that consumerism will save an ailing economy and restore public confidence in the health of the country at large. During the interwar period, mass culture took a firm hold on Western societies, causing the division between public and private to break down and for local events, products, and outlooks to become increasingly national and international in scale.